Penerapan Model Active Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Di MTs Khairotul Islamiyah Pematangsiantar - Zulia Almaida Siregar; Ika Okta Kirana; Zulaini Masruroh Nasution; , Nani Hidayati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The method or strategy in the learning process is something that is important to support the success of learning objectives. Some educational institutions still apply the classical learning model so that educators feel they are still in a comfortable condition in carrying out the learning process. Meanwhile, nowadays the demands of the curriculum and the development of science and technology greatly affect the learning process. Educators should use learning models that make students more creative, think critically, be active and be able to develop ideas in their own way. This of course can improve student learning outcomes. As for the results of this study, it can be concluded that the Active learning model applied at MTs Khoirotul Islamiyah, Pematangsintar City, is manifested in several components that influence each other, namely learning objectives, selection of learning methods and media that are appropriate to the content/subject matter as well as teachers and students. These components are designed so that in practice students are more active in learning. This strategy is applied to make it easy for students to know, understand, appreciate, and apply the material conveyed by the teacher in student life, so that the goals of studying economics can be realized. There are two supporting factors for the implementation of Active learning in Economics learning including; teacher professionalism, facilities and infrastructure. Meanwhile, there are two factors that hinder the realization of Active learning strategies in Economics learning, namely: the teacher's lack of preparation in planning learning scenarios and the lack of student motivation due to different backgrounds, such as the social environment, cultural environment, learning styles, economic conditions and level of intelligence.